Implementation Of Game Based Learning Model Using Snakes And Ladders Media To Improve Student Learning Activeness - Anastasya, Ronauli; Ammy, Putri Maisyarah; Simarmata, Hotnida (STABN RADEN WIJAYA WONOGIRI, 2024)
This study aims to improve student learning activity by implementing a game-based learning model using snakes and ladders media. The background of this study is based on the low learning activity of students such as being passive during discussions, less enthusiastic about answering teacher questions, and being reluctant to participate in learning activities as well as learning activities that have not been able to encourage active involvement both individually and in groups. This study was conducted in class III of SD N 066055 Medan using the Classroom Action Research (CAR) method which was implemented in two cycles. The increase in learning activity can be seen from the results of the questionnaire in the pre-cycle to cycle II. In the pre-cycle, the number of students in the Active and Very Active categories was only 6 people (31.6%). In cycle I it increased to 10 people (52.6%), and in cycle II it increased again to 15 people (78.9%). This shows that the implementation of Game Based Learning through snakes and ladders media has proven to have a positive effect and helps improve student learning activity.